Language Empowering in Character Building (Pemberdayaan Bahasa dalam Pembentukan Karakter) - Kamsinah Kamsinah (Masyarakat Linguistik Indonesia Universitas Andalas, 2013)
Character building is the most important thing to do as it is a striving system which underly behavior (Freud). Even more, good character is more to be praised than outstanding talent. Most talents are to some extent a gift. Good character, however, is not given to us. we have to build it peace by peace by thought, choice, courage, and determination. So important it is that it is said that if there is no more character every thing is lost (Mahatma Gandhi). The best way to build it isÂ to develop the function of all individual potential, including cognitive, affective, and psychomotoric aspects simultanously in the context of socio-cultural interaction (in family, in school, and in society). Character is gained by nature and nurture. It can be done begin from the golden age to the old one through the three character building components: moral knowing, moral feeling, and moral action as suggested by Lickona. They make it possible since human beings, as the best-formed creature of all, are the ones and the only creature posessing culture, and that, they can educate and be educated in terms of the model of person of character. Everybody must have character. Therefore, to apply Lickona's, one must empower her/his language, in which she/he/ perform her/his competence in using language creativity (Chomsky) in both ordinary and literary language. In this case, Buginese language is used as the sample.